2020
DOI: 10.1002/jper.19-0467
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome analysis of smoker palatal mucosa identifies multiple downregulated innate immunity genes

Abstract: BackgroundSmoking has significant negative impact on periodontal health and treatment outcomes. The molecular effects of smoking on oral immune homeostasis have not been fully elucidated. The present study aimed to provide a comprehensive assessment of smoking‐associated gene expression changes in healthy palatal mucosa and to identify potentially implicated immunologic pathways.MethodsPalatal biopsies, in the form of connective tissue grafts, were obtained from periodontally healthy smokers and non‐smokers. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The significantly higher expression of IL33 in healing gingiva and its strong association with miRNA suggest that IL33 may also play a significant regulatory role in oral wound healing. In a recent report from this laboratory, IL33 expression levels in palatal gingiva was strongly negatively associated with cotinine levels and smokers’ gingiva expressed significantly lower IL33 levels than non‐smokers under homeostatic conditions 24 . This finding, along with the results of the present study, raises the possibility that IL‐33 could emerge as a possible target for improvement of impaired healing in smokers.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The significantly higher expression of IL33 in healing gingiva and its strong association with miRNA suggest that IL33 may also play a significant regulatory role in oral wound healing. In a recent report from this laboratory, IL33 expression levels in palatal gingiva was strongly negatively associated with cotinine levels and smokers’ gingiva expressed significantly lower IL33 levels than non‐smokers under homeostatic conditions 24 . This finding, along with the results of the present study, raises the possibility that IL‐33 could emerge as a possible target for improvement of impaired healing in smokers.…”
Section: Discussionsupporting
confidence: 77%
“…Fixed biopsy samples were processed as previously detailed 24 . Slides were stained with primary antibody against SERPINB1 and IL‐33 and followed by a horseradish peroxidase detection system and development in 3,3′‐diaminobenzidine.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were: aged 21 to 38 years (age limits based on evidence of delayed wound healing in older adults 28 ); no coagulation disorders or other systemic disease; no medications affecting periodontal status in the previous 6 months; no allergy to study medications or materials; no pregnancy/lactation/contraceptive medication; no tobacco or marijuana use (non‐smoker status verified by exhaled air carbon monoxide as previously described 29 ); full‐mouth plaque score 30 and full‐mouth bleeding score ≤ 20% at study entry; adequate anteroposterior arch length for required wound size and spacing; able to easily tolerate maxillary impression making and use of palatal template; no contraindication to receiving PHT, other study medications (anesthetics, analgesics), or gingival surgery. Study exclusion criteria were: untreated caries; inadequate endodontic therapy or tooth mobility > 1 on maxillary teeth; untreated periodontitis; previous surgery on the palate.…”
Section: Methodsmentioning
confidence: 99%
“…In a follow‐up study, the same group found that smokers express 830 contrasting genes compared with nonsmokers. These differentially expressed genes were associated with innate immunity and antimicrobial response and were downregulated in smokers 103 …”
Section: Palatal Soft Tissue Wound Healingmentioning
confidence: 99%
“…These differentially expressed genes were associated with innate immunity and antimicrobial response and were downregulated in smokers. 103…”
Section: Genes Implicated In Palatal Soft-tissue Wound Healingmentioning
confidence: 99%